Financial performance and cash flow: Evidence from the US banking industry - Rompotis, Gerasimos G. (Research Papers in Economics and Finance, 2024)
This study examines the relationship between cash flow and financial performance with a sample of 122 American banks covering the period 2019-2022. Panel data analysis is applied. Financial performance is computed as the Return on Assets (ROA) and Return on Equity (ROE). The explanatory variables used are the net cash flow, free cash flow, cash flow from operating activities, cash flow from investing activities, cash flow from financing activities, size of banks, the leverage ratio, i.e., total liabilities to total assets, the liquidity ratio, i.e., current assets to current liabilities, and the efficiency ratio, i.e., total revenue to total assets. The results provide evidence of a negative relationship between financial performance and net cash flow. This is also the case for cash flow from investment and financing activities. On the contrary, the relationship of free cash flow with performance is positive. On the other explanatory variables, leverage and efficiency are positively related to financial performance.